Contemporary body experiences: from body as image trough body as devenir (Fractal: Journal of Psychology, 2009)
This work looks for to supply a perspective about the body and its relations to the subjectivity, culture and history. We depart from the conception of body as multiplicity - "bodyness", body experienced -, through which it is possible to visualize its historical inscriptions and its possibilities to resist, beyond contemporary obviousness body has assumed. It is concluded that the rupture to historical inscriptions - both the hardness of the Brazilian military regime, as the contemporary fluidity and spectacularization - may be made through the redemption of creation and invention movement in the body, and contemporary dance can serve as a possible way.